ANALYZING THE WORK PROFESSIONALISM OF TEACHERS AT SMA NEGERI 1 AMURANG TIMUR - Kindangen, Natalia Shareen; Pangemanan, Sifrid S.; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Human resource management is needed to improve the effectiveness of human resources in the field of schooling, is also a process of dealing with various problems in the field of teachers to be able to support learning activities in the classroom in order to achieve predetermined goals. The purpose is to find out the work professionalism of teachers at SMA Negeri 1 Amurang Timur. This study is a qualitative method used to examine the conditions of natural objects. Â The result of this research is the work professionalism of teachers at this school has been fulfilled, but there are some teachers who do not meet the standards of some indicators. There are some indicator which affects their performance at work. The conclusion is several informant it can be said to be professional because it has good potential in guiding and educating students, but there are still some informant who are good teachers but cannot be said to be professional because they have not met the standards that have been set. For high school principals SMA Negeri 1 Amurang Timur need to pay more attention to discipline at school and more attention to teachers in schools who are still less productive.Â Keywords: human resource management, teachers, professionalism